Treatment-seeking behaviour, awareness and preventive practice toward malaria in Abu Ushar, Gezira state, Sudan: a household survey experience from a rural area - Elfatih A. Hasabo; Rawan I. Khalid; Ghassan E. Mustafa; Ruaa E. Taha; Riham S. Abdalla; Reham A. Mohammed; Mazin S. Haroun; Rawaa Adil; Riham A. Khalil; Rawaa M. Mansour; Reham K. Mohamed; Heitham Awadalla (Malaria Journal, 2022)
Abstract Background Usage of mosquito bed nets and the practice of other prevention methods are essential for the prevention of malaria in endemic areas. Proper community knowledge about malaria and prompt treatment-seeking behaviour for early diagnosis and treatment are crucial for eliminating the disease. This study aimed to assess the awareness, treatment-seeking behaviour, and prevention practices towards malaria in Abu Ushar, Gezira State, Sudan. Methods A community-based, cross-sectional study was conducted in March 2021, including 310 households in Abu Ushar, Aljazeera, Sudan. Data were collected through face-to-face interviews with head of the household using an interviewer-administered questionnaire. Data were entered and analysed using R software. Results A total of 310 households were enrolled in this study. Sixty per cent had children under the age of 5 years. The majority of these households (94.8%) had a history of malaria in the past 12 months. Overall, awareness of malaria was good; 197 (63.5%) households had bed nets in their houses; 75.8% of total households identified fever with shivering as a symptom of malaria. Regarding treatment-seeking behaviour, 77.9% seek treatment from the nearby primary health centre, and 60% seek treatment within the first day. Only 45.3% stated that everyone in the household sleeps under bed nets. Conclusion High awareness about malaria and preventive measures was found among participants in households. Most households had previous infections with malaria. Therefore, an interventional programme should be established in this area to reduce this high rate of malaria.